Kardinal Domenico Ginnasi und das Kirchlein San Sebastiano in Ostia - Ruotolo, Roberta (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2021)
"Cardinal Domenico Ginnasi and the small church of Saint Sebastian in Ostia" - The church of Saint Sebastian belongs to the sacred buildings of Ostia. It was a significant construction used also as a funerary area (in the ancient times), as we can read in many archival sources, like reports about the state of the diocese or lists of the properties of different ancient real estate registries. Local hagiographic traditions about Ostia's martyrs form the basis for Christian memories but the history of the church of Saint Sebastian shows something new and unknown.